x^{v-1}e^{-μx}/(1-ae^{-x})[0,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\infty} \frac{x^{v-1}e^{-μx}}{1-ae^{-x}}dx=Γ(v)Φ(a,v,μ)  (|a| \lt 1,\,v \gt 1,\,μ \gt 0)\\
&(2)  \displaystyle\int_0^{\infty} \frac{x^{v-1}}{e^{μx}-a}dx=\frac{Γ(v)}{μ^v}Φ(a,μ,1)  (|a| \lt 1,\,v \gt 0,\,μ \gt 0)\\
\end{alignat}








<証明>

\begin{alignat}{2}
(1)  \displaystyle\int_0^{\infty} \frac{x^{v-1}e^{-μx}}{1-ae^{-x}}dx&=\displaystyle\int_0^{\infty} x^{v-1}e^{-μx}\left\{\displaystyle\sum_{n=0}^{\infty} (ae^{-x})^n\right\}dx\\
&=\displaystyle\sum_{n=0}^{\infty}a^n \displaystyle\int_0^{\infty} x^{v-1}e^{-(μ+n)x}dx\\
\end{alignat}\((μ+n)x=t\) と置きます。[\((μ+n)dx=dt\)]
\begin{alignat}{2}
&=\displaystyle\sum_0^{\infty} a^n \displaystyle\int_0^{\infty} \left(\frac{t}{μ+n}\right)^{v-1}e^{-t} \cdot \frac{1}{μ+n}dt\\
&=\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{(μ+n)^v}\displaystyle\int_0^{\infty} t^{v-1}e^{-t}dt\\
&=Γ(v)\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{(μ+n)^v}=Γ(v)Φ(a,v,μ)\\
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{v-1}e^{-μx}}{1-ae^{-x}}dx=Γ(v)Φ(a,v,μ)$$







\begin{alignat}{2}
(1)  \displaystyle\int_0^{\infty} \frac{x^{v-1}}{e^{μx}-a}dx&=\displaystyle\int_0^{\infty} \frac{x^{v-1}e^{-μx}}{1-ae^{-μx}}dx=\displaystyle\int_0^{\infty} x^{v-1}e^{-μx}\left\{\displaystyle\sum_{n=0}^{\infty} (ae^{-μx})^n\right\}dx\\
&=\displaystyle\sum_{n=0}^{\infty}a^n \displaystyle\int_0^{\infty} x^{v-1}e^{-(n+1)μx}dx\\
\end{alignat}\((n+1)μx=t\) と置きます。[\((n+1)μdx=dt\)]
\begin{alignat}{2}
&=\displaystyle\sum_{n=0}^{\infty} a^n \displaystyle\int_0^{\infty} \left\{\frac{t}{(n+1)μ}\right\}^{v-1}e^{-t} \cdot \frac{1}{(n+1)μ}dt\\
&=\frac{1}{μ^v}\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{(n+1)^v}\displaystyle\int_0^{\infty} t^{v-1}e^{-t}dt\\
&=\frac{Γ(v)}{μ^v}\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{(n+1)^μ}=\frac{Γ(v)}{μ^v}Φ(a,μ,1)\\
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{v-1}}{e^{μx}-a}dx=\frac{Γ(v)}{μ^v}Φ(a,μ,1)$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です